The rhetoric of dream crazy memes: Attitudes about CSR, race, patriotism, and racial capitalism - Greer III, Richard A. (Kansas State University, 2020)
In this thesis, I am interested in the rhetoric Dream Crazy Memes, particularly as they speak to perspectives of Nike as a responsible social actor, racial tensions and anxieties in American society, athlete activism and anthem protests, and partisan engagement. I conduct a rhetorical analysis of two genres of Dream Crazy Memes; one which revisits a historical lineage of critiques of Nike’s relationship to sweatshop labor, and one which compares and contrasts Kaepernick and military service members. I argue that the Dream Crazy Meme is used to express and perpetuate attitudes about Kaepernick and Nike, of course, but also about tensions and anxieties in American society, including race, patriotism, protest, and CSR. I contend that scholars should weight equally mode, circulation, and rhetorical strategies when analyzing internet memes and I exhibit how such an analysis which attends to all three might be carried out. Dream Crazy Memes express disparate attitudes in response to CSR, race, patriotism, and racial capitalism. They also exhibit strategies of incongruence, synecdoche, framing, and political ambivalence in order to express those attitudes.
Keywords: Corporate Social Responsibility; Nike; Rhetorical analysis; Memes; Rhetoric of race; Patriotism